2006
DOI: 10.1093/jn/136.5.1287
|View full text |Cite
|
Sign up to set email alerts
|

Combined Lycopene and Vitamin E Treatment Suppresses the Growth of PC-346C Human Prostate Cancer Cells in Nude Mice

Abstract: Epidemiologic studies have repeatedly associated a high intake of lycopene and vitamin E with reduced prostate cancer risk. The present study examined the ability of the 2 compounds to reduce tumor growth and prostate-specific antigen (PSA) plasma levels in the PC-346C orthotopic mouse model of human prostate cancer. Three days after intraprostatic tumor injection, NMRI nu/nu mice were administered a daily oral dose of synthetic lycopene [5 or 50 mg/kg body weight (BW)], vitamin E in the form of alpha-tocopher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 67 publications
3
49
1
2
Order By: Relevance
“…Lycopene is a promising component for the chemoprevention of prostate cancer [30] Regular intake of lycopene has been repeatedly associated with a reduced risk of developing the disease [31]. The significant inverse association detected between lycopene intake and prostate cancer in this study is consistent with the findings that evidence exists for inverse associations of dietary intake of lycopene with PC [13] [32] [33].…”
Section: Discussionsupporting
confidence: 87%
“…Lycopene is a promising component for the chemoprevention of prostate cancer [30] Regular intake of lycopene has been repeatedly associated with a reduced risk of developing the disease [31]. The significant inverse association detected between lycopene intake and prostate cancer in this study is consistent with the findings that evidence exists for inverse associations of dietary intake of lycopene with PC [13] [32] [33].…”
Section: Discussionsupporting
confidence: 87%
“…At dosages of 100 and 300 mg/kg lycopene, the tumor growth rates were inhibited 55.6 and 75.8%, respectively. In contrast, Limpens et al [52] used the PC-346C orthotopic mouse model of prostate cancer but found no effect on tumor volume when lycopene was administered orally at 5 or 50 mg/kg. However, tumor volume was reduced with lycopene was combined with α-tocopherol acetate.…”
Section: In Vivo Studies Of Lycopenementioning
confidence: 95%
“…Androgen is an important biological effector of prostate cancer progression (17). Many studies have demonstrated that phytochemicals can effectively inhibit the apoptosis and proliferation of prostate cancer cells (18)(19)(20)(21)(22). Chun et al reported inhibition of cell viability and apoptosis of Pca cells treated by andrographolide, which is extracted from a medicinal plant (23).…”
Section: Introductionmentioning
confidence: 99%